Radar observations of winds and turbulence in the stratosphere and mesosphere - Woodman Pollitt, Ronald Francisco (1974)
A technique for the observation of radar echoes from stratospheric and mesospheric heights has been developed at the Jicamarca Radio Observatory. Signals are detected at the altitude ranges between 10–35 km and from 55–85 km with powers from many to several tens of decibels above noise level. The three most important frequency spectrum characteristics-power, Doppler shift and spectrum width-are observed in real time. The power levels as well as the spectral width are explained in terms of turbulent layers, with a thickness of the order of 100 m, in regions with a positive potential temperature or electron density vertical gradients. Continuous wind velocity records are obtained with a precision of the order of 0.02–0.2 m sec−1 for the vertical component and 0.20–2 m sec−1 for the horizontal, with a time resolution of the order of 1 min. The highest precisions are obtained at stratosphere heights. Fluctuations in velocity in the mesosphere are observed at the shortest gravity wave periods with amplitudes of the order of 1 m sec−1 for the vertical component and of 10 m sec−1 for the horizontal. Tidal components at these altitudes are not as large as predicted by theory. A technique to obtain the power, the Doppler shift, and the width of the frequency spectrum of the echo signals from only two points of the correlation function is described.